User experience: Assessing the effectiveness of internet booking services - Md. Tap, Abu Osman; Hussien, Idyawati; Mahmud, Murni (2010)
Despite the undeniable importance of usability and utility, one should not forget that people use Internet booking service for variety of reasons or in essence overlooked the vital intent. Online booking systems challenge the effectiveness of traditional way of booking process. Therefore the effectiveness of the task is crucial to support the user to complete the tasks. User Experience (UX) is basically a constant “good-bad” feeling towards any products or service to finish a task. Standard heuristics evaluation has been performed in UX to measure if the perceived usability of the online booking based on the perceived utility matched to the user's satisfaction. This paper indicates that several design features do not entirely conform to the usability standard and design principles. The finding shows that the users experience some difficulties in completing the task; however, they proceed in order to get competitive prices. They also attribute the difficulties to their incautious and negligent without realizing the design features have lead them to experience human error in the online booking system.